Patterns of direct-to-consumer geriatric urgent care by telemedicine during the Covid-19 pandemic - Flávio Tocci Moreira; Tarso Augusto Duenhas Accorsi; Karine De Amicis Lima; Renata Albaladejo Morbeck; Eduardo Cordioli; Carlos Henrique Sartorato Pedrotti (2023)
-